การพัฒนาฟิล์มบางนาโนเพื่อยืดอายุการเก็บรักษาของมะม่วง: รายงานการวิจัย(ปีที่1) - ปราณี โรจน์สิทธิศักดิ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2014)
This two year project is to study and develop the fonnulation of nano thin film solution containing chitosan to prolong the shelf-life of mango Namdokmai". The physiology of mango after coating with chitosan solution and stored at 25 °C and 14°C was investigated. In the first year project, nano thin film solution containing chitosan was developed and characterized. The results suggested that chitosan with molecular weight of 65,000 -410,000 g/mol is well dissolved in acetic acid with the concentration of 0.5% (v/v). Tween 80® can enhance the film to stick continuously on the hydrophobic surface of materials. However, overdose ofTween 80® caused foaming in the fonnulation. In general, nano thin film fonnulation containing chitosan should be added 0.1 % (w/v) Tween 80® in 1 % chitosan (w/v). Acetic acid with the concentration of 0.5% (v/v) should be used as a solvent of chitosan and the dipping technique is to be used in this project.